Comparative Genomic In Situ Hybridization and the Possible Role of Retroelements in the Karyotypic Evolution of Three Akodontini Species - Naiara Pereira Araújo; Gustavo Campos Silva Kuhn; Flávia Nunes Vieira; Thaís Queiroz Morcatty; Adriano Pereira Paglia; Marta Svartman (International Journal of Genomics)
South American Akodontini rodents are characterized by a large number of chromosome rearrangements. Among them, the genus Akodon has been extensively analyzed with classical and molecular cytogenetics, which allowed the identification of a large number of intra- and interspecific chromosomal variation due to Robertsonian rearrangements, pericentric inversions, and heterochromatin additions/deletions. In order to shed some light on the cause of these rearrangements, we comparatively analyzed the karyotypes of three Akodontini species, Akodon cursor (2n = 14, FN = 19), A. montensis (2n = 24, FN = 42), and Necromys lasiurus (2n = 34, FN = 34), after GTG- and CBG-banding. The karyotypes differed by Robertsonian rearrangements, pericentric inversions, centromere repositioning, and heterochromatin variation. Genome comparisons were performed through interspecific fluorescent in situ hybridization (FISH) with total genomic DNAs of each species as probes (GISH). Our results revealed considerable conservation of the euchromatic portions among the three karyotypes suggesting that they mostly differ in their heterochromatic regions. FISH was also performed to assess the distribution of telomeric sequences, long and short interspersed repetitive elements (LINE-1 and B1 SINE) and of the endogenous retrovirus mysTR in the genomes of the three species. The results led us to infer that transposable elements have played an important role in the enormous chromosome variation found in Akodontini.